FAKTOR-FAKTOR YANG MEMPENGARUHI HIPERTENSI PADA KEHAMILAN - Megawati Sinambela; Nur Mala Sari (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2018)
Hypertension is a state of elevated blood pressure that can lead to various complications, such as stroke, and kidney failure. Hypertension in pregnancy is a blood pressure higher than 140/90 mmHg that caused by pregnancy itself, and it has the potential to cause serious disruption in pregnancy.This study aims to determine the factors that affect hypertension in pregnancy in the Working Area of Public Center Of Pancur Batu, Pancur Batu Sub-District, Deli Serdang District In 2018, with type of quantitative research, analytie case control design. The population in this study is the total number of pregnant women who experience hypertension consisting of case and control group of 72 people. Sampling technique used Total Sampling. Data was collected by interview by using questionnaire. Data analysis was done by bivariate with Chi-Square test at 95% confidence level, Î±=5%.The result showed that there was influence between age (p=0,016), parity (p=0,028), obesity (p=0,018), descent (p=0,000), physical activity (p=0,000), excessive food comsumption (p=0,001), stress (p=0,031) on hypertension in pregnancy. Multivariate analysis results that the risk level of hypertension in pregnancy is affected by heredity, physical activity and excessive food consumption of 99,5%.For Pancur batu Community Health Center, Pancur Batu Subdistrict, Deli Serdang Regency, to make policy in order to give information about hypertension problem in pregnancy, danger, and how to overcome hypertension in pregnant women.